2010
DOI: 10.1177/1046496410377359
|View full text |Cite
|
Sign up to set email alerts
|

Deliberation and Diversity: Perceptions of Small Group Discussions by Race and Ethnicity

Abstract: One of the challenges facing public deliberation scholars and practitioners is to identify deliberative processes that address inequities in interaction and foster active participation among all members of ethnically or racially diverse groups. This study draws from cocultural communication theory and uses mixed methodology to examine the experiences of citizens assigned to racially/ ethnically diverse small groups who participated in “By the People: Dialogues in Democracy”—a national/local initiative and publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Individual differences form the basis for organizational diversity and also shape people's perceptions, attitudes, values, beliefs and behaviours. A number of studies (e.g., Abdel-Monem, Bingham, Marincic, & Tomkins, 2010;David A Harrison, Price, Gavin, & Florey, 2002;Jehn & Chatman, 2000;D. C. Lau & Murnighan., 1998;Reagans, 2005) have suggested that similarities in demographic attributes enhance mutual liking and team functioning and that demographic diversity decreases both social interaction and social integration.…”
Section: Organizational Diversity and Job Performancementioning
confidence: 99%
“…Individual differences form the basis for organizational diversity and also shape people's perceptions, attitudes, values, beliefs and behaviours. A number of studies (e.g., Abdel-Monem, Bingham, Marincic, & Tomkins, 2010;David A Harrison, Price, Gavin, & Florey, 2002;Jehn & Chatman, 2000;D. C. Lau & Murnighan., 1998;Reagans, 2005) have suggested that similarities in demographic attributes enhance mutual liking and team functioning and that demographic diversity decreases both social interaction and social integration.…”
Section: Organizational Diversity and Job Performancementioning
confidence: 99%
“…The sample’s specific characteristics also include the participants’ equal education level and similar social status. On one hand, this may be an advantage because the participants are more equal and are not distinct concerning social differences; on the other hand, these factors’ influence on the participants’ attitude change and (the perception of) deliberativeness could also be measured in other contexts, as already partly tested (e.g., Abdel-Monem et al, 2010) but again not in similar experimental conditions. Our sample consists of participants from school collectives (preexisting groups), which may have predisposed participants to group interactions, particularly in the non-facilitated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Only little scholarly attention has been paid to facilitation and its effects in the field of deliberation research. Scholars (e.g., Abdel-Monem, Bingham, Marincic, & Tomkins, 2010; Karpowitz & Mendelberg, 2011; Landwehr, 2014; Setälä & Herne, 2014) recognize the lack of studies testing the effects of facilitation and call for experiments that manipulate facilitation, along with research designs that include control groups without professional facilitation, which would be required for a comprehensive assessment of the effects of facilitation. There is a clear need for randomized experimental research designs with sufficient control on both individual and group levels (Karpowitz & Mendelberg, 2011).…”
mentioning
confidence: 99%
“…Regardless of how this affects voting outcomes, participating scientists may enhance their science communication skills through seeing the same proposal presented and received via diverse perspectives. Actively acknowledging diversity and its role in decision-making may also improve participants' satisfaction (Abdel-Monem, Bingham, Marincic, & Tomkins, 2010).…”
Section: Presenter Diversitymentioning
confidence: 99%